Synthesis of copolymers based on benzo[1, 2-b:4, 5-b′]difuran and fluorinated quinoxaline derivatives and their photovoltaic properties. (12th June 2015) - Cong, Zhiyuan; Zhao, Baofeng; Wu, Haimei; Guo, Zhaoqi; Wang, Weiping; Luo, Guoping; Xu, Jin; Xia, Yangjun; Gao, Chao; An, Zhongwei
Abstract: Two alternating polymers based on two-dimensional conjugated benzo[1, 2- b :4, 5- b ′]difuran and fluorinated quinoxaline derivatives were synthesized. Their structures are poly4, 8-bis(2, 3-(dioctyl)thiophen-5-yl)-benzo[1, 2- b :4, 5- b ′]difuran- alt -5, 8-bis(thiophen-2-yl)-6-fluoro-2, 3-bis(3-octyloxyphenyl) quinoxaline (P1, mono F) and poly4, 8-bis(2, 3-(dioctyl)thiophen-5-yl)-benzo[1, 2- b :4, 5- b ′]difuran- alt -5, 8-bis(thiophen-2-yl)-6, 7-difluoro-2, 3-bis(3-octyloxyphenyl) quinoxaline (P2, double F). UV–vis absorption measurements show that the difluorinated polymerP2 exists a higher absorption in comparison with the mono fluorinated polymerP1 either in the solution or in the film. Electrochemical measurements confirm that the polymerP2 displays low energy levels (−5.30 eV and −3.25 eV) of both highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) in comparison with those ofP1 (−5.25 eV and −3.20 eV). Photovoltaic cells with conventional device configuration of ITO/PEDOT:PSS/polymer:PC71 BM/PFN/Al were fabricated. The power conversion efficiency (PCE) of the optimized polymer solar cells (PSCs) based onP1 reaches 2.22% with a current density of 5.28 mA/cm 2 . However, a high PCE of 4.44% with a high current density of 8.74 mA/cm 2 was obtained for the double fluorinated polymerP2 based device. Graphical abstract: Highlights: Two alternating polymers based on benzo[1, 2- b :4, 5- b ′]difuran and fluorinated quinoxaline derivatives were synthesized. The difluorinated polymerP2 displays deep HOMO energy level. A high PCE of 4.44% was obtained for the double fluorinated polymer P2 based solar cells.